Capnocytophaga Induced Acute Necrotizing and Exudative Pericarditis with Abscess Formation - Alexa Bello; Alejandro Castaneda; Abhay Vakil; Joseph Varon; Salim Surani (Case Reports in Infectious Diseases)
We present the case of a 55-year-old gentleman, with bilateral pulmonary embolism and a large pericardial effusion that lead to a pericardial window with evacuation of creamy pus. Gram stains were negative, with culture growing Capnocytophaga. Pathology revealed acute necrotizing and exudative changes, including frank abscess formation. In developed countries, pericardial abscess and acute pericarditis are uncommon due to availability of broad-spectrum antibiotics. Pericardial abscess due to Capnocytophaga is even more uncommon.